GdCrO3: a potential candidate for low temperature magnetic refrigeration. (4th July 2018) - Mahana, Sudipta; Manju, U; Topwal, D
Abstract: Detailed magnetic studies of polycrystalline GdCrO3 show a spectrum of interesting features, such as temperature induced magnetization reversal, spin flipping and spin reorientation, etc, which arise due to the competing magnetic interactions within and between Cr and Gd-sublattices. It also exhibits a giant magnetocaloric effect (MCE) with a maximum entropy change of 36.97 J kg −1 K −1, an adiabatic temperature change of 19.12 K and a refrigeration capacity of 542 J kg −1 for a field change of 7 T at low temperatures. Such an exceptionally large MCE arises from the suppression of the spin entropy associated with the suppression of spin reorientation transition, in addition to the Gd-ordering, which makes it one of the best candidates for magnetic refrigeration among all known potential low temperature magnetic refrigerants.